Estimation of Seismic Centroid Moment Tensor Using Ocean Bottom Pressure Gauges as Seismometers. Issue 21 (4th November 2017) - Kubota, Tatsuya; Saito, Tatsuhiko; Suzuki, Wataru; Hino, Ryota
Abstract: We examined the dynamic pressure change at the seafloor to estimate the centroid moment tensor solutions of the largest and second largest foreshocks ( Mw 7.2 and 6.5) of the 2011 Tohoku‐Oki earthquake. Combination of onshore broadband seismograms and high‐frequency ( 20–200 s) seafloor pressure records provided the resolution of the horizontal locations of the centroids, consistent with the results of tsunami inversion using the long‐period (≳10 min) seafloor pressure records although the depth was not constrained well, whereas the source locations were poorly constrained by the onshore seismic data alone. Also, the waveforms synthesized from the estimated CMT solution demonstrated the validity of the theoretical relationship between pressure change and vertical acceleration at the seafloor. The results of this study suggest that offshore pressure records can be utilized as offshore seismograms, which would be greatly useful for revealing the source process of offshore earthquakes. Key Points: We estimated the CMT of offshore M 7 earthquakes using onshore seismometers and offshore pressure gauges The horizontal location of the centroid is well constrained by using offshore pressure gauges as seismometers Observed pressure‐change waveforms show the theoretical predicted relationship between pressure and vertical acceleration